Success and decline: Top 10 tennis players follow a biphasic curse - Guillaume, M.; Len, S.; Tafflet, M.; Quinquis, L.; Montalvan, B.; Schaal, K.; Nassif, H.; Desgorces, F. D.; Toussaint, J. F. (Medicine & Science in Sports & Exercise, 2011)
Introduction: The victory percentages for tennis players who entered the top 10 women and men rankings show various evolutions related to age and time since 1968.